Research on Urban Traffic Industrial Management under Big Data: Taking Traffic Congestion as an Example - Yi Zhang; Shuwang Yang; Hang Zhang (Journal of Advanced Transportation)
This paper establishes a prediction model of traffic flow, where three cycle dependent components are used to model three characteristics of traffic data, respectively. CNN is used to extract spatial features, and the combination of LSTM and attention mechanism is used to dynamically capture the influence of historical period on target period. Finally, the results are obtained by weighted integration of each component. Its prediction result is more accurate, which can provide reference for governance of urban transportation industry under the background of big data.